INFLUENCE OF VARYING LEVELS OF BERGAFAT ON PERFORMANCE OF BROILER CHICKS - M. Ali; M. Sharif; J. I. Sultan; S. Rehman; K. Farooq; M. L. Khan (Journal of Animal and Plant Sciences, 2012)
The present study was conducted to examine the effect of bergafat HTL-306 on feed intake, live weight gain, organ characteristics and feed cost analysis of broilers in a completely randomized design. Four iso-caloric and iso-nitrogenous broiler starter and finisher diets were formulated using 0 (control), 2, 4 and 6% levels of bergafat. One hundred and twenty day old broiler chicks were divided randomly into twelve experimental units of ten chicks each. Each experimental diet was fed to three replicates. Broiler starter diets were fed during 0-4 weeks while finisher diets during 5-6 weeks of age. At the end of the experiment, two chicks from each replicate were slaughtered to determine the organ characteristics. It was observed that live weight gain and feed conversion ratio were significantly (p<0.05) better in birds fed diets containing 4 and 6% bergafat. Dressing percentage increased significantly (p<0.05) while average visceral fat percentage decreased significantly (p>0.05) with supplementation of bergafat in the diet. Feed cost/kg live weight gain was lower in birds fed diets containing 4% bergafat. In conclusion supplementation of bergafat in broiler diets up to 4% resulted in improved live weight gain and economical broiler production.
Keywords: Broiler; bergafat; growth performance; organ characteristics; feed cost analysis